Social health determinants and education need about sexually transmitted infections in pregnant adolescents - Guevara-Valtier, Milton Carlos (Universidad de Sonora, 2020)
Introduction: In recent years there has been an increase and a greater precocity of sexual initiation causing an increase in the incidence of adolescent pregnancy, but its prevalence varies worldwide. Sexually Transmitted Infections are recognized as a major public health problem but can be prevented. Objective: Know the Social Health Determinants present for a higher risk of early pregnancy and identify education need during the adolescence stage regarding knowledge of Sexually Transmitted Infections. Methodology: A cross-sectional descriptive design was used. The sample was comprised by 60 pregnant adolescents ranging in age from 10 to 19 years. A scale regarding knowledge of the human immunodeficiency virus and other sexually transmitted infections was used with a Cronbach's Alpha ranging from .66 to .88. Results: It was found that 38.3% of the surveyed sample has a history of adolescent pregnancies in the family. Forty percent of them were unaware of the transmission methods of the Human Immunodeficiency Virus and 50% are unaware of the transmission of the Human Papilloma Virus. In general, 50% are unaware of sexually transmitted infections. Conclusion: The main social health determinants found were family factors such as family type (two-parent family) and history of adolescent pregnancies in the family; regarding sexual and reproductive factors there is the beginning of the first sexual relation at an early age, having more than two sexual partners, previous use of contraceptive methods, and lack of knowledge.